Digitalization of legal services A study of business models of legal lech companies digitalizing the legal industry - Elkhalki, Radwan; Elkhalki, Nathalie (My University, 2022)
The legal industry is still traditional and conservative where the lawyers typically charge by the hour (Simmons, 2015; Kronblad, 2019; 2021). But as society develops, so does the legal industry. We are moving from the lawyer’s market to the consumer market through digitalization where services within law are being more accessible and transparent. (Kronblad, 2019; 2021) With this study, the researchers aim to understand digitalization within contract law. That includes the business models that are being used, the main differences in how these services are being delivered and their different revenue models, and their strengths and weaknesses. To reach a satisfying result, the researchers have used a more overlooking review of twenty (20) different companies as well as a narrower review of five (5) different companies. Looking at the results, there are only a few revenue models that are being used such as subscriptions, freemium, and add-ons, and almost every company still uses hourly rates to some extent. The strengths and weaknesses are similar in all companies within the study, no matter which business model they are using. The strengths are increased scalability and competitive pricing for the companies and flexibility and ease for consumers, whereas weaknesses can be linked to difficulties to predict the amount of one-on-one help that is needed as well as the high amount of one-on-one help from lawyers that still is needed as well as lack of trust for the customer. The weaknesses are mainly connected to the insecurities on how much to charge, get people to try online services, and decrease the amount of help from lawyers.
Keywords: business model; legal tech; digitalization; lawyer